ENDOPHYTIC FUNGI IN Paraserianthes falcataria: PRODUCTION OF INDOLE ACETIC ACID - REINE SUCI WULANDARI; ROSA SURYANTINI (Microbiology Indonesia, 2019)
Identification of endophytic fungi in Paraserianthes falcatria is the effort of the potential of endophytic fungi as phytohormone producer.  Phytohormone is needed to spur shoot and root initiation.  This study in P. falcatariais necessary when woody of P. falcataria decreases every year.  The aimed of the study were to identify endophytic fungi from leaves, twigs, and roots of P. falcataria, and determine IAA content from endophytic fungi.  Isolates that were grown from leaves, twigs and roots cuttings on PDA, were identified based on micro- and macromorphology. Determining of IAA content was counted with spectrophotometer vis based on a calibration curve from the standard solution.  The results were obtained 10 of isolates fungi from leaves, twigs, and roots.  But from 10, only nine isolates that could be identified.  They were Aspergillus sp., Acremonium sp., Cladosporium sp., Trichoderma sp. 1, Phytium sp., Rhizoctonia sp., Trichoderma sp. 2, Hormiscium sp. 1 and Hormiscium sp. 2.  Production of indole acetic acid (IAA) from Cladosporium sp. had the highest content than others (311 ppm).  The lowest IAA content (51.97 ppm) was produced by the Rhizoctonia sp.  The study can be continued to find out their abilities as PGPF agents and biopesticides of P. falcataria seedlings.